Head injuries among FIS World Cup alpine and freestyle skiers and snowboarders: a 7-year cohort study - Steenstrup, S. E.; Bere, T.; Bahr, R. (British Journal of Sports Medicine, 2014)
Background: Traumatic brain injury is the leading cause of death for skiers and snowboarders. Fatal head injuries have also occurred at the International Ski Federation (FIS) World Cup (WC) level. We therefore wanted to describe the risk of head injuries across disciplines and sex among WC skiers and snowboarders. Method: We conducted retrospective interviews with FIS WC athletes at the end of seven consecutive seasons (2006-2013) to register injuries sustained during the competitive season. Head injuries were classified as `head/face` injuries and did not include neck or cervical spine injuries. To calculate the exposure, we extracted data from the official FIS website for all WC competitions for each of the athletes interviewed. Results: A total of 2080 injuries were reported during seven WC seasons. Of these, 245 (11.8%) were head/face injuries. Of the 245 head/face injuries reported, nervous system injuries/concussions were the most common (81.6%) and 58 of these were severe (23.7%). The injury incidence per 1000 competition runs was higher in freestyle (1.8, 95% CI 1.2 to 2.4) than in alpine skiing (0.9, 95% CI 0.6 to 1.2; risk ratio (RR) 2.05, 95% CI 1.25 to 3.46) and snowboard (1.0, 95% CI 0.6 to 1.3; RR 1.85, 95% CI 1.15 to 2.99). Women had a higher injury incidence (5.8, 95% CI 4.8 to 6.9) versus men (3.9, 95% CI 3.2 to 4.6; RR 1.48, 95% CI 1.15 to 1.90) throughout the season (per 100 athletes). Conclusions: The majority of head/face injuries were nervous system injuries/concussions and one in four injuries was severe. Freestyle skiers had the highest overall head injury incidence. Across all disciplines, the injury incidence was higher in women than in men.